Efecto analgésico intra postoperatorio del remifentanilo y el clorhidrato de lidocaína en perras adultas sometidas a ovariohisterectomía - Romero Toala, Roberto Holger (2022)
The present investigation was carried out at the "Guillem" Veterinary Clinic in Portoviejo canton with the objective of evaluating the analgesic effect of remifentanil and lidocaine hydrochloride used intraoperatively and postoperatively in adult female dogs undergoing Ovariohysterectomy. The study was carried out in 30 healthy female canines aged 2 to 3 years, divided into two groups, using the ompletely Randomized Design that served to identify the effect of remifentanil and lidocaine hydrochloride in each of the independent samples. During the intraoperative period, each of the canines was evaluated in different parameters such as respiratory rate (RR), capillary refill (seconds), peripheral blood pressure (mm Hg), temperature (T ºC), pulse oximetry (%), the extubation time (minutes) and the recovery time (minutes) in relation to the aforementioned analgesics, interpreted as indicators of analgesic degree, each parameter was evaluated every 15 minutes after the administration of the protocol, through surgery parameters were measured every 3 minutes, average time in which the statistical values were considered, verifying that there is no significant difference between the two treatments, it was obtained as a result that lidocaine hydrochloride is the most recommended due to the greater stability that provides to the dogs with their vital signs.